Analysis of Factors Driving Technological Development Against Changes in Learning Period IN the Covid 19 Era - Indah Aryani; Nuri Aslami (Journal of Indonesian Management, 2022)
The COVID-19 pandemic that hit Indonesia suddenly caused a shift from the face-to-face learning system to an online learning system. The smoothness of the online learning process is influenced by various factors that can hinder or hinder the smooth flow of online learning. Based on these results, this study was conducted to determine the factors that encourage online learning and how the criteria for these factors affect online learning. Technology acts as a means of interaction between teachers and students in the implementation of online learning. In addition, technology also helps educators easily provide learning materials, enabling them to continue learning without face-to-face contact. The implementation of online learning certainly presents obstacles that become challenges for educators of academic culture, such as values, attitudes, knowledge, skills, and the readiness of institutions and infrastructure related to technology. This research design uses descriptive qualitative research. The sample size is 65 of the total 80 population. The data collection method in this study used the no-test method by distributing closed questionnaires. Methods of data analysis using percentages and averages. Based on data analysis, the driving factor for online learning at a high standard is 77.27%, and the inhibiting factor at a high standard is 64.01%. From this, we can conclude that the drivers and barriers to online learning are at a high standard. Teacher motivation factors in online learning are adequate facilities and infrastructure, teacher motivation in planning online learning processes, teacher proficiency in using techniques, and communication between teachers and parents, and teacher online learning, the problem is teacher difficulties. It is difficult to implement interactions between teachers and parents, teachers and students when providing material.